Preparation method of anti-corrosion coating of pole-mounted isolating switch

By combining dopamine-modified graphene oxide and cellulose nanocrystals with aqueous epoxy resin, an anticorrosion coating for the column is prepared, which solves the problem of the equipment's susceptibility to corrosion and significantly improves the anti-corrosion and rust performance and the service life of the equipment.

CN119592169APending Publication Date: 2025-03-11SHENZHEN POWER SUPPLY BUREAU
View PDF 2 Cites 0 Cited by

Patent Information

Application Number
CN202411900822.5
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-12-23
Publication Date
2025-03-11

AI Technical Summary

Technical Problem

Due to long-term exposure of the column isolation switches, they are prone to oxidation, corrosion and rust, resulting in reduced equipment reliability and shortened service life.

Method used

A dopamine-modified graphene oxide (DA-GO) and cellulose nanocrystalline (CNC) composite material combined with aqueous epoxy resin (WEP) was used to prepare an anticorrosion coating of the column isolation switch. The coating ensures uniform dispersion and good adhesion of the material through ultrasonic dispersion and uniform stirring.

Benefits of technology

This anti-corrosion coating significantly improves the corrosion and rust resistance of the column isolation switch, has good water, acid and alkali resistance and salt spray resistance, extends the service life of the equipment and reduces maintenance costs.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119592169A_ABST
    Figure CN119592169A_ABST
Patent Text Reader

Abstract

The invention provides a preparation method of an anti-corrosion coating of a pole-mounted isolating switch. The preparation method mainly comprises the following steps: firstly, preparing a dopamine modified graphene oxide (DA-GO) composite material; secondly, preparing cellulose nanocrystallines (CNC); then mixing the DA-GO with CNC (computer numerical control) to prepare composite slurry; finally, the composite slurry is mixed with water-borne epoxy resin (WEP), a curing agent is added, the surface of a pole-mounted disconnecting switch part is coated with the composite slurry, an anti-corrosion coating is formed after curing, the surface of a pole-mounted switch metal exposed part is evenly coated with the prepared coating, and the anti-corrosion coating is obtained after curing. The performances such as water resistance, acid and alkali resistance and salt spray resistance are obviously improved.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of anti-corrosion of a pole-mounted isolating switch, and in particular to a method for preparing an anti-corrosion coating for a pole-mounted isolating switch. Background Art

[0002] Due to long-term exposure to the outdoors, the pole-mounted disconnector is susceptible to oxidation corrosion and rust on its metal surface due to factors such as high temperature, high humidity, and dirt, which in turn affects the reliable operation of the equipment. According to statistics, more than 30% of pole-mounted disconnector failures in the distribution network are caused by oxidation corrosion, which significantly affects the safe operation of the distribution network and the service life of the equipment. Therefore, it is particularly important to carry out anti-oxidation and anti-corrosion treatment on the metal surface of the pole-mounted disconnector.

[0003] Anti-oxidation coating can provide a protective barrier for the metal surface, preventing the metal from direct contact with oxygen and other corrosive media in the environment, thereby slowing down or preventing the corrosion process. In the application of pole-mounted disconnectors, anti-oxidation coating can significantly improve the corrosion resistance of the equipment, extend the service life of the equipment, reduce maintenance costs, and improve the safety and reliability of distribution network operation.

[0004] Among various organic coatings, epoxy coatings are widely used for anti-corrosion protection because of their good adhesion to metal surfaces and excellent chemical properties. Pure epoxy resin coatings (EP) are brittle, low in density, and poor in resistance to mechanical shock and thermal shock. The coating will inevitably be scratched during use, resulting in damage and cracking of the coating. In addition, the condensation and cross-linking of organic molecules during the curing process of the coating will affect the density of the coating, resulting in a large number of micropores, microcracks and other defects, which will become diffusion channels for corrosive ions, thus causing coating failure. Summary of the invention

[0005] The purpose of the present invention is to provide an anti-corrosion coating for a pole-mounted disconnector and a preparation method thereof. The prepared coating is evenly coated on the surface of the exposed metal part of the pole-mounted switch, and the anti-corrosion coating is obtained after curing. The coating has good anti-corrosion and anti-rust effects, and the water resistance, acid and alkali resistance and salt spray resistance are significantly improved.

[0006] To achieve the purpose of the present invention, an embodiment of the present invention provides a method for preparing an anti-corrosion coating of a pole-mounted disconnector, comprising the following steps:

[0007] (1) Preparation of a dopamine modified graphene oxide (DA-GO) composite material, comprising: ultrasonically dispersing graphene oxide (GO), mixing an appropriate amount of dopamine hydrochloride (DA) with the GO dispersion, stirring evenly, centrifuging and washing the dispersion to obtain a dopamine modified graphene oxide (DA-GO) composite material;

[0008] (2) Preparation of cellulose nanocrystals (CNC), comprising: using cellulose as a raw material, hydrolyzing amorphous regions of cellulose by acid hydrolysis, then centrifuging to remove the acid, and further washing with water to obtain a CNC dispersion with good dispersibility;

[0009] (3) mixing DA-GO and CNC by ultrasonication and stirring to disperse them uniformly to obtain DA-GO@CNC composite slurry;

[0010] (4) Add DA-GO@CNC composite slurry to waterborne epoxy resin (WEP), stir and disperse it evenly, then add curing agent and stir, apply DA-GO@CNC / WEP coating on the surface of the column disconnector components, and obtain an anti-corrosion coating after curing.

[0011] Preferably, the concentration of the graphene oxide dispersion in step (1) is 0.2-2 mg / mL, and the ultrasonic time is 0.5-5 h.

[0012] Preferably, the mass ratio of dopamine hydrochloride to graphene oxide in step (1) is 1:10 to 5:1.

[0013] Preferably, the stirring temperature in step (1) is 25 to 45° C., and the stirring time is 4 to 12 h.

[0014] Preferably, the cellulose raw material in step (2) can be cellulose powder, bamboo pulp, wood pulp, etc.

[0015] Preferably, the acid used in the acid hydrolysis in step (2) is one of sulfuric acid, hydrochloric acid, phosphoric acid, oxalic acid and hydrobromic acid; and the reaction time and temperature are adjusted according to the acid used.

[0016] Preferably, in step (2), the mass ratio of DA-GO to CNC is 20:1 to 1:5; and the mixing ultrasonic time is 0.5 to 6 hours.

[0017] Preferably, the amount of the DA-GO@CNC composite material added in step (2) accounts for 0.1 to 2.0 wt% of the mass of WPU.

[0018] Preferably, the mass ratio of the WPU to the curing agent in step (2) is 2:1 to 4:1.

[0019] Preferably, the curing temperature in step (2) is 35 to 55° C., the curing time is 4 to 24 hours, and the coating thickness in step (2) is 50 to 150 μm.

[0020] The anti-corrosion coating prepared by the method described above has the following advantages and beneficial effects:

[0021] (1) Traditional anti-corrosion coatings are mostly solvent-based coatings, which seriously affect the environment and ecology. In order to control environmental pollution and protect the health of workers / users, my country has formulated a series of measures to limit the use of high volatile organic compound (VOC) coatings. The amount of volatile compounds released by water-based epoxy coatings is extremely low, and it is an environmentally friendly coating. Both DA-GO and CNC composite fillers can be prepared and dispersed in water. The preparation process of DA-GO@CNC / WEP coatings is environmentally friendly and pollution-free.

[0022] (2) Graphene is an emerging two-dimensional nanomaterial with excellent impermeability, stability, and mechanical properties. However, the easy aggregation of graphene makes it difficult to evenly disperse in epoxy resin emulsion. The self-polymerization characteristics of dopamine and the functional groups it contains are used to repair the surface defects of graphene oxide, and self-polymerization reaction occurs on the surface of graphene oxide to form polydopamine to improve its dispersibility in water, which is beneficial to its dispersion in water-based epoxy resin and improves the adhesion of the coating. Secondly, dopamine modification can enhance the interaction between graphene oxide and other nanocomposite fillers, thereby enhancing the coating performance.

[0023] (3) Nanocellulose crystallites (CNC) have high strength, high Young's modulus and excellent barrier properties. CNC prepared by the acid method has abundant surface groups, good dispersibility in aqueous media, and interacts with dopamine-modified graphene oxide to achieve a synergistic enhancement effect. By changing the preparation method and conditions, CNC with different surface functional groups and adjustable scale and crystallinity can be obtained, and the preferred CNC can be obtained to improve the anti-corrosion and anti-wear properties of the coating.

[0024] (4) The prepared DA-GO@CNC / WEP anti-corrosion coating has good anti-corrosion and anti-rust effects, and its water resistance, acid and alkali resistance, and salt spray resistance are significantly improved, and it has good application prospects. BRIEF DESCRIPTION OF THE DRAWINGS

[0025] In order to more clearly illustrate the embodiments of the present invention or the technical solutions in the prior art, the drawings required for use in the embodiments or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are only some embodiments of the present invention. For ordinary technicians in this field, without paying creative labor, other drawings obtained based on these drawings still belong to the scope of the present invention.

[0026] Figure 1 The present invention is a flowchart of a method for preparing an anti-corrosion coating for a pole-mounted disconnector in an embodiment of the present invention. DETAILED DESCRIPTION

[0027] The detailed description of the drawings is intended as an illustration of the current embodiment of the present application, and is not intended to represent the only form in which the present application can be implemented. It should be understood that the same or equivalent functions can be accomplished by different embodiments intended to be included in the spirit and scope of the present application.

[0028] Example 1

[0029] The present embodiment provides a method for preparing an anti-corrosion coating for a pole-mounted disconnector, comprising the following steps:

[0030] (1) 1.21 g of Tris was added to 1000 mL of deionized water, and the pH was set to 8.5 using dilute hydrochloric acid to titrate the solution. 0.1 g of graphene oxide (GO) was added to 200 mL of buffer and ultrasonically dispersed for 1 h. 0.1 g of dopamine hydrochloride (DA) and GO dispersion were mixed, stirred at 35 °C for 24 h, and the solution was centrifuged at 4500 rpm, then rinsed three times with ethanol and deionized water to obtain a dopamine-modified graphene oxide (DA-GO) composite material.

[0031] (2) Preparation of cellulose nanocrystals (CNC) by sulfuric acid hydrolysis: 64% sulfuric acid was used to hydrolyze the cellulose raw material at 55°C for 1 hour; the acid solution was then removed by centrifugation, and the mixture was washed by centrifugation with deionized water until the pH was neutral, thereby obtaining a CNC dispersion with sulfonate groups.

[0032] (3) Mix a certain amount of DA-GO and CNC (mass ratio of 10:1) by ultrasonic treatment, stir and disperse evenly to obtain DA-GO@CNC composite slurry. Add 0.5wt% of DA-GO@CNC composite slurry to 10.0g of waterborne epoxy resin (WEP), stir and disperse evenly, then add 5.0g of curing agent and continue stirring for 5min. Apply the DA-GO@CNC / WEP coating on the surface of dry and clean pole-mounted disconnector parts, transfer the coated coating to 40℃ for curing for 24h to obtain the anti-corrosion coating of the pole-mounted disconnector.

[0033] Example 2

[0034] The present embodiment provides a method for preparing an anti-corrosion coating for a pole-mounted disconnector, comprising the following steps:

[0035] (1) 1.21 g of Tris was added to 1000 mL of deionized water, and the pH was set to 8.5 using dilute hydrochloric acid to titrate the solution. 0.1 g of graphene oxide (GO) was added to 200 mL of buffer and ultrasonically dispersed for 1 h. 0.1 g of dopamine hydrochloride (DA) and GO dispersion were mixed, stirred at 35 °C for 24 h, and the solution was centrifuged at 4500 rpm, then rinsed three times with ethanol and deionized water to obtain a dopamine-modified graphene oxide (DA-GO) composite material.

[0036] (2) Preparation of cellulose nanocrystals (CNC) by sulfuric acid hydrolysis: 64% sulfuric acid was used to hydrolyze the cellulose raw material at 55°C for 1 hour; the acid solution was then removed by centrifugation, and the mixture was washed by centrifugation with deionized water until the pH was neutral, thereby obtaining a CNC dispersion with sulfonate groups.

[0037] (3) A certain amount of DA-GO and CNC (mass ratio of 20:1) were mixed by ultrasonication and stirred to disperse evenly to obtain DA-GO.

[0038] @CNC composite slurry. Add 0.1wt% DA-GO@CNC composite slurry to 10.0g waterborne epoxy resin (WEP), stir and disperse evenly, then add 5.0g curing agent and continue stirring for 5min. Apply DA-GO@CNC / WEP coating on the surface of dry and clean pole-mounted disconnector parts, transfer the coated coating to 40℃ for curing for 24h to obtain the anti-corrosion coating for pole-mounted disconnector.

[0039] Example 3

[0040] The present embodiment provides a method for preparing an anti-corrosion coating for a pole-mounted disconnector, comprising the following steps:

[0041] (1) 1.21 g of Tris was added to 1000 mL of deionized water, and the pH was set to 8.5 using dilute hydrochloric acid to titrate the solution. 0.1 g of graphene oxide (GO) was added to 200 mL of buffer and ultrasonically dispersed for 1 h. 0.1 g of dopamine hydrochloride (DA) and GO dispersion were mixed, stirred at 35 °C for 24 h, and the solution was centrifuged at 4500 rpm, then rinsed three times with ethanol and deionized water to obtain a dopamine-modified graphene oxide (DA-GO) composite material.

[0042] (2) Preparation of cellulose nanocrystals (CNC) by sulfuric acid hydrolysis: 64% sulfuric acid was used to hydrolyze the cellulose raw material at 55°C for 1 hour; the acid solution was then removed by centrifugation, and the mixture was washed by centrifugation with deionized water until the pH was neutral, thereby obtaining a CNC dispersion with sulfonate groups.

[0043] (3) Ultrasonic mixing of a certain amount of DA-GO and CNC (mass ratio of 10:1) was performed, and the mixture was stirred and dispersed evenly to obtain a DA-GO@CNC composite slurry. 1.0wt% of the DA-GO@CNC composite slurry was added to 10.0g of waterborne epoxy resin (WEP), and the mixture was stirred and dispersed evenly. Then, 5.0g of curing agent was added, and the stirring was continued for 5min. The DA-GO@CNC / WEP coating was applied to the surface of the dry and clean pole-mounted disconnector components, and the applied coating was transferred to 40°C for curing for 24h to obtain a pole-mounted disconnector anti-corrosion coating.

[0044] Comparative Example 1

[0045] Compared with Example 1, the difference is that no CNC filler is added:

[0046] (1) 1.21 g of Tris was added to 1000 mL of deionized water, and the pH was set to 8.5 using dilute hydrochloric acid to titrate the solution. 0.1 g of graphene oxide (GO) was added to 200 mL of buffer and ultrasonically dispersed for 1 h. 0.1 g of dopamine hydrochloride (DA) and GO dispersion were mixed, stirred at 35 °C for 24 h, and the solution was centrifuged at 4500 rpm, then rinsed three times with ethanol and deionized water to obtain a dopamine-modified graphene oxide (DA-GO) composite material.

[0047] (2) Add 0.5 wt% DA-GO slurry to 10.0 g waterborne epoxy resin (WEP), stir and disperse evenly, then add 5.0 g curing agent and continue stirring for 5 min. Apply DA-GO / WEP coating on the surface of dry and clean pole-mounted disconnector parts, transfer the coated coating to 40°C for curing for 24 h, and obtain the pole-mounted disconnector anti-corrosion coating.

[0048] Comparative Example 2

[0049] Compared with Example 1, the difference is that no DA-GO filler is added:

[0050] (1) Preparation of cellulose nanocrystals (CNC) by sulfuric acid hydrolysis: 64% sulfuric acid was used to hydrolyze the cellulose raw material at 55°C for 1 hour; the acid solution was then removed by centrifugation, and the mixture was washed by centrifugation with deionized water until the pH was neutral, thereby obtaining a CNC dispersion with sulfonate groups.

[0051] (2) Add 0.5 wt% CNC to 10.0 g of waterborne epoxy resin (WEP), stir and disperse evenly, then add 5.0 g of curing agent and continue stirring for 5 min. Apply the CNC / WEP coating on the surface of the dry and clean pole-mounted disconnector parts, transfer the coated coating to 40°C for curing for 24 h, and obtain the pole-mounted disconnector anti-corrosion coating.

[0052] Comparative Example 3

[0053] Compared with Example 1, the difference is that the graphene oxide is not modified with dopamine:

[0054] (1) Graphene oxide is ultrasonically dispersed in water.

[0055] (2) Preparation of cellulose nanocrystals (CNC) by sulfuric acid hydrolysis: 64% sulfuric acid was used to hydrolyze the cellulose raw material at 55°C for 1 hour; the acid solution was then removed by centrifugation, and the mixture was washed by centrifugation with deionized water until the pH was neutral, thereby obtaining a CNC dispersion with sulfonate groups.

[0056] (3) Mix a certain amount of GO and CNC (mass ratio of 10:1) by ultrasonic treatment, stir and disperse evenly to obtain GO / CNC composite slurry. Add 0.5wt% of GO / CNC composite slurry to 10.0g of waterborne epoxy resin (WEP), stir and disperse evenly, then add 5.0g of curing agent and continue stirring for 5min. Apply the GO@CNC / WEP coating on the dry and clean surface of the pole-mounted disconnector parts, transfer the coated coating to 40°C for curing for 24h to obtain the anti-corrosion coating for the pole-mounted disconnector.

[0057] Comparative Example 4

[0058] Compared with Example 1, the difference is that DA-GO and CNC filler are not added, and water-based epoxy resin is directly used as the coating: the water-based epoxy resin and the curing agent are mixed and stirred in a mass ratio of 2:1 for 5 minutes, and then coated on the surface of the dry and clean pole-mounted disconnector parts, and the coated coating is transferred to 40°C for curing for 24 hours to obtain the pole-mounted disconnector anti-corrosion coating.

[0059] The detection methods and performance data of the anti-corrosion integrated coatings described in Examples 1 to 3 and the anti-corrosion integrated coatings described in Comparative Examples 1 to 4 are shown in Table 1:

[0060] Table 1

[0061]

[0062]

[0063] The above disclosure is only the preferred embodiment of the present invention, which certainly cannot be used to limit the scope of the present invention. Therefore, equivalent changes made according to the claims of the present invention are still within the scope of the present invention.

Claims

1. A method for preparing an anti-corrosion coating for a pole-mounted disconnector, comprising the following steps: (1) Preparation of dopamine modified graphene oxide (DA-GO) composite material, comprising: Ultrasonic dispersion of graphene oxide (GO) was performed, and an appropriate amount of dopamine hydrochloride (DA) was mixed with the GO dispersion, and the mixture was stirred evenly. The dispersion was centrifuged and washed to obtain a dopamine-modified graphene oxide (DA-GO) composite material; (2) Preparation of cellulose nanocrystals (CNC), comprising: using cellulose as a raw material, hydrolyzing amorphous regions of cellulose by acid hydrolysis, then centrifuging to remove the acid, and further washing with water to obtain a CNC dispersion with good dispersibility; (3) mixing DA-GO and CNC by ultrasonication and stirring to disperse them uniformly to obtain DA-GO@CNC composite slurry; (4) Add DA-GO@CNC composite slurry to waterborne epoxy resin (WEP), stir and disperse it evenly, then add curing agent and stir, apply DA-GO@CNC / WEP coating on the surface of the column disconnector components, and obtain an anti-corrosion coating after curing.

2. The preparation method according to claim 1, characterized in that: The concentration of the graphene oxide dispersion in step (1) is 0.2-2 mg / mL, and the ultrasonic time is 0.5-5 h.

3. The preparation method according to claim 1, characterized in that: The mass ratio of dopamine hydrochloride to graphene oxide in step (1) is 1:10 to 5:

1.

4. The preparation method according to claim 1, characterized in that: The stirring temperature in step (1) is 25 to 45° C., and the stirring time is 4 to 12 hours.

5. The preparation method according to claim 1, characterized in that: The cellulose raw material in step (2) can be cellulose powder, bamboo pulp, wood pulp, etc.

6. The preparation method according to claim 1, characterized in that: The acid used in the acidolysis in step (2) is one of sulfuric acid, hydrochloric acid, phosphoric acid, oxalic acid and hydrobromic acid; the reaction time and temperature are adjusted according to the acid used.

7. The preparation method according to claim 1, characterized in that: In step (2), the mass ratio of DA-GO to CNC is 20:1 to 1:5; and the mixing ultrasonic time is 0.5 to 6 hours.

8. The preparation method according to claim 1, characterized in that: The added amount of the DA-GO@CNC composite material in step (2) accounts for 0.1 to 2.0 wt% of the WPU mass ratio.

9. The preparation method according to claim 1, characterized in that: The mass ratio of WPU to curing agent in step (2) is 2:1 to 4:

1.

10. The preparation method according to claim 1, characterized in that: The curing temperature of step (2) is 35-55° C., the curing time is 4-24 hours, and the coating thickness of step (2) is 50-150 μm.

Citation Information

Patent Citations

  • Dual-modified graphene oxide modified waterborne epoxy resin anticorrosive paint

    CN115029025A

  • Nano cellulose / graphene modified waterproof coating and preparation method thereof

    CN117004276A